A rare cause of epididymo-orchitis - Patil, Siddanagouda B.; Patil, Basavesh S.; Patil, Santosh R.; Kundargi, Vinay S.; Shariff, Nawaz A. (International Journal of Research in Medical Sciences, 2024)
Epididymo-orchitis is an inflammatory lesion of the testis and epididymis with a lymphocytic exudate. Patients with acute epididymo-orchitis typically present with scrotal pain, swelling, tenderness and fever. Here, we present a patient with scrotal pain and hemiscrotal swelling as the main complaints; however further investigations revealed a completely different and rare diagnosis. Zinner’s syndrome is a very rare developmental anomaly of the Wolffian duct. To date, only about 200 cases have been diagnosed. It is a triad of unilateral renal agenesis, ipsilateral seminal vesicle cyst and ejaculatory duct obstruction. Some patients remain asymptomatic and discovered incidentally, while others present with symptoms related to seminal vesicle cysts or ejaculatory duct obstruction: voiding or ejaculatory difficulty or pain. Treatment options include transurethral or transrectal aspiration and percutaneous drainage, however both are linked to an increased risk of recurrence. Symptomatic, complicated and recurrent cyst will require excision of the cyst, either laparoscopically or robotically.